Sequelae after modified Fontan operation: postoperative haemodynamic data and organ function. Issue 2 (August 1997) - Kaulitz, R.; Luhmer, I.; Bergmann, F.; Rodeck, B.; Hausdorf, G.
Abstract : OBJECTIVE: To investigate the specific sequelae of the Fontan operation, and particularly the potential sequelae of chronically elevated systemic venous pressure. DESIGN: A retrospective analysis of clinical and haemodynamic data and evaluation of organ function in 80 surviving patients undergoing modified Fontan operation for various forms of underlying functionally univentricular hearts. PATIENTS: 65 patients (81%) who had undergone a total cavopulmonary anastomosis and 15 an atriopulmonary anastomosis. Follow up ranged from 12 to 106 months (mean 54 (SD 23) months). RESULTS: 62 patients underwent postoperative cardiac catheterisation (mean systemic venous pressure 10.5 (2.5) mm Hg and cardiac index 3.1 (0.7) l/min/m2). Older age at operation was significantly correlated with both higher systemic venous pressure and lower cardiac index. Atrial arrhythmia was documented on Holter electrocardiogram in 17%. Protein losing enteropathy (with abnormal alpha 1-antitrypsin clearance) was found in 2/80 patients (2.5%). Ten patients had hypoproteinaemia, with a significantly higher incidence in patients after total cavopulmonary anastomosis and young age at operation. Liver function tests reflecting liver synthesis and metabolism were normal in all, whereas mild cholestasis was found in nearly 30%-predominantly in patients with a cardiac index of < 3 l/min/m2 (P = 0.045). Five patients (6.2%) developed atrial thrombosis. Coagulation factor analysis in 44 patients showed protein C deficiency in 11 (25%); laboratory signs of activation of the coagulation system were found in four of these (9%). None of the abnormal laboratory indices was significantly related to underlying cardiac malformation, postoperative systemic venous pressure, or follow up interval. CONCLUSIONS: A high proportion of clinically asymptomatic patients had abnormal laboratory findings on mid-term follow up. Detailed evaluation of organ function is necessary to detect the need for further diagnostic procedures before clinical symptoms develop.